2006
DOI: 10.1002/cvde.200606491
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Metal Thin Films and Patterned IrO2 Nanowires Deposited Using Iridium(I) Carbonyl Precursors

Abstract: Highly volatile iridium(I) carbonyl complexes (1-5) with three anionic fluorinated chelates, namely ketoiminate, aminoalkoxide, or iminoalkoxide, have been synthesized and their physical properties relevant to CVD are evaluated. A single-crystal Xray diffraction (XRD) study on Ir(CO) 2 (amakNMe 2 ) (3) confirms a square-planar geometry with two cis-orientated carbonyl ligands. Metallic iridium, polycrystalline IrO 2 thin films, or even patterned IrO 2 nanowires are deposited using Ir(CO) 2 (hfdaN n Pr) (5) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
4
32
0
Order By: Relevance
“…Two distinct peaks, representing the 4f 7/2 and 4f 5/2 spin states were evident for all 4 GPMs, with binding energies at 61.4, 51.5, 72.0 and 45.6 eV for the 4f 7/2 spin state of G–Ir, G–Os, G–Pt and G–Re, respectively. These values largely correspond to the binding energy of the respective metal elements (G–Ir and G–Pt) and metal oxides (G–Os and G–Re) based on previous studies,3134 suggesting that the metals are most likely existing in different environments for different metal–graphene hybrids. In addition, the atomic percentages of the metal present in each material are summarized in Table 1 as well, with iridium present in the largest amount in the hybrid material as compared to the other three materials.…”
Section: Resultssupporting
confidence: 75%
“…Two distinct peaks, representing the 4f 7/2 and 4f 5/2 spin states were evident for all 4 GPMs, with binding energies at 61.4, 51.5, 72.0 and 45.6 eV for the 4f 7/2 spin state of G–Ir, G–Os, G–Pt and G–Re, respectively. These values largely correspond to the binding energy of the respective metal elements (G–Ir and G–Pt) and metal oxides (G–Os and G–Re) based on previous studies,3134 suggesting that the metals are most likely existing in different environments for different metal–graphene hybrids. In addition, the atomic percentages of the metal present in each material are summarized in Table 1 as well, with iridium present in the largest amount in the hybrid material as compared to the other three materials.…”
Section: Resultssupporting
confidence: 75%
“…On the other hand, the dimeric compound [Me 2 In{OC(CF 3 ) 2 CH 2 NHCH 2 CH 2 -OMe}] 2 contains a centrosymmetric, four-membered In 2 O 2 ring, where each indium metal atom adopts a distorted trigonal bipyramidal geometry with two methyl groups being in equatorial positions ( Figure 6). 40 A number of other metal complexes (Ti, 70 Zr, 70 Hf, 70 Ru, 39 Pd, 38 Ir, 215 and Cu 37,43 ) based on fluorinated amino-and imino-alkoxide ligands have also been reported. X-ray diffraction studies revealed a monomeric structure in all cases, with the anticipated coordination according to the type of ligand framework.…”
Section: Synthetic Methodsmentioning
confidence: 97%
“…In turn, they proved to be valuable precursors for deposition of thin films made of quite pure Pd, 16 Ir, 17 Ru, 18 and Cu 19 metals with a low level of carbon and oxygen impurities, as well as polycrystalline IrO 2 thin films, or even patterned IrO 2 nanowires. 17 Gallium derivatives Ga{OL} 2 Cl, where LO = OC(CF 3 ) 2 -CH 2 NMe 2 , OC(CF 3 ) 2 CH 2 C(Me)=NMe, were similarly prepared from GaCl 3 and the corresponding ligand sodium salt (Scheme 10). 20 Single-crystal X-ray diffraction studies revealed mononuclear compounds in a trigonal-bipyramidal (tbp) geometry with chloride and alkoxy groups occupying the equatorial sites and the nitrogen donors located at the axial positions.…”
Section: Late Transition and Main Group Metal Complexes Based On Iminmentioning
confidence: 98%